Sustainable architectural design and land-use application to civic centres in Ghana: the case of Damongo - Lukman Kura Abraham Safo; Daniel Yaw Addai Duah; Stephen Biliyitorb Liwur (Urban, Planning and Transport Research)
The country’s ever-growing population and numerous administrative areas and centres for decentralisation, good administration, and efficient use of the country’s resources have allowed for the construction of several administrative buildings. However, these spaces are typically modified or do not meet the architectural and planning criteria of administrative centres due to shortcomings in planning standards as well as a lack of sustainable design standards and principles. Using an observational data collection method and qualitative research methods, the results of the study examined the appraisal of the proposed design. The study proposed a sustainable design that would help minimise the usage of vast lands for only administrative purposes and provide developable lands for the fast-growing urban population. The study analysed three sites for their suitability. Details of the proposed design are emphasised in the rest of the paper.